Assessment of the participation rate and effectiveness of upper gastrointestinal cancer screening in China: a multicenter population-based screening study - Song, Song; Liu, Han; Geng, Xianyi; Chen, Ru; Zheng, Rongshou; Li, Ni; Chen, Wanqing; Wei, Wenqiang; Ren, Jiansong (Endoscopy, 2025)
This study estimated the participation rate and effectiveness of endoscopic screening of upper gastrointestinal cancer (UGIC) in China.From 2014 to 2015, we recruited 192805 adults from seven cities in China to build a prospective cohort for UGIC screening, including esophageal cancer and gastric cancer. Overall, 39991 participants were at high risk for UGIC according to an established risk score system and were recommended for endoscopic examination. Participation rates were reported, and their associated factors were explored. After inverse probability of treatment weighting (IPTW) based on propensity scores, Poisson regression was used to estimate the incidence rate ratio (IRR) and 95%CI for UGIC incidence and mortality between screened and non-screened groups from cohort entry until 31 December 2021.10442 participants underwent endoscopy, giving a participation rate of 26.1%. Higher participation was observed among individuals with higher education levels, history of upper gastrointestinal diseases, and family history of cancer. After a median follow-up of 6.8 years (interquartile range 6.7–6.9), UGIC incidences after IPTW were 94.6 per 100000 person-years in the screened group and 84.7 per 100000 person-years in the non-screened group. The weighted UGIC mortality rates were 13.1 and 33.4 per 100 000 person-years, respectively. The screened group had significantly lower UGIC mortality than the non-screened group, with a weighted IRR of 0.39 (95%CI 0.19–0.82).Participation in endoscopic screening among a high-risk UGIC population in China was low. We found that one-time endoscopic screening significantly reduced mortality caused by UGIC.